Puno: landscapes, figures and history to build a model - Cetraro Cardó, César (2008)
The present work is a diagnosis of the reality of Puno that highlights the conditions of poverty in which 80.4% of the inhabitants live, despite the improvement of certain indicators over the last 40 years in aspects such as literacy and the educational level. Agriculture continues to be the main economic activity of the people of Puno, followed by services. Geographical, political and administrative conditions are described with informative tables based on the most recent statistics.